Management of Complicated Colonic Diverticulosis - Ariadi Humardani; Ari F Syam; Murdani Abdullah; Ibrahim Basyir; Arman A Abdullah (The Indonesian Society for Digestive Endoscopy, 2006)
Prevalence of diverticular disease has been increasing worldwide in concert with the development of industrial era and the alteration of diet pattern to low dietary fiber. Mean age of patients is 60 years; peak incidence at age more than 50 years, 20% less than 50 years, 2-8% less than 40 years. About 50 - 90% of diverticular disease are left-sided especially sigmoid, while in Asian people are mostly right sided. The usual complaint of patient is abdominal pain. Complications that may occur due to diverticulosis are diverticulitis, abscess, fistula, obstruction and bleeding. The presence of complicated diverticulosis can be evaluated by plain X-rays, CT-scan, barium with contrast, ultrasonography and colonoscopy in addition of laboratory examination. The management of complicated diverticulosis usually consists of combination of medical therapy and surgery. Proper and immediate treatment will influence the prognosis of patients. Keywords: diverticular diseases, diverticulitis, abscess, fistula, obstruction, bleeding